The Influence of Ethical Behaviors of Leaders, Workplace Gratitude, and Employee Well-Being on Employee Green Behaviors in the Industrial Sector - Marilyn Raranta; Tiarapuspa (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
Global climate change and increasing awareness of sustainability have encouraged organizations in Jakarta to adopt more environmentally friendly business practices, one of which is through the implementation of Employee Green Behaviors (EGB). However, encouraging employees to engage in green behavior is not easy, especially in industrial sectors that often focus on productivity and profitability. In this context, this research explores the role of leaders' ethical behavior, workplace gratitude, and employee well-being in fostering EGB. Leaders who demonstrate ethical behavior play an important role in creating a work climate that supports green behavior, while gratitude in the workplace can increase employee engagement in prosocial behavior. In addition, employee well-being, which includes physical, mental and social aspects, has been proven to mediate the relationship between leader ethical behavior, gratitude and EGB. This research focuses on industry in Jakarta, with the aim of filling the knowledge gap regarding the relationship between these three variables in the context of developing countries, especially Indonesia, which has unique challenges and opportunities in implementing sustainability policies.